2006
DOI: 10.1042/cs20050372
|View full text |Cite
|
Sign up to set email alerts
|

Detection of elevated pulmonary capillary wedge pressure in elderly patients with various cardiac disorders by the Valsalva manoeuvre

Abstract: In the present study, we assessed whether elevated (> or =15 mmHg) PCWP (pulmonary capillary wedge pressure) can be detected using the blood pressure response to the Valsalva manoeuvre in a group of elderly patients with various cardiac disorders, including atrial fibrillation and valvular heart disease, and healthy elderly controls. The Valsalva manoeuvre was performed in 93 patients (71+/-4 years) and 28 healthy controls (70+/-4 years) undergoing right-sided cardiac catheterization. Blood pressure was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, other studies PAR (9,17,23,33) using the Finapres or the Vericor have shown close correlation between cardiac filling pressure and just PAR, which would be much easier to derive from a bedside photoplethysmography signal than combining multiple variables. Some studies (3,9,23,38) have used a higher expiratory effort, as high as 40 mmHg, and one study (33) used a longer expiratory effort duration of 15 s. The expiratory effort needs to be consistent, because PAR is lower when expiratory effort is higher (10,21,32). We chose parameters that patients with heart and/or lung disease would be more likely to achieve (23).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, other studies PAR (9,17,23,33) using the Finapres or the Vericor have shown close correlation between cardiac filling pressure and just PAR, which would be much easier to derive from a bedside photoplethysmography signal than combining multiple variables. Some studies (3,9,23,38) have used a higher expiratory effort, as high as 40 mmHg, and one study (33) used a longer expiratory effort duration of 15 s. The expiratory effort needs to be consistent, because PAR is lower when expiratory effort is higher (10,21,32). We chose parameters that patients with heart and/or lung disease would be more likely to achieve (23).…”
Section: Discussionmentioning
confidence: 95%
“…Two disadvantages of performing a bedside Valsalva maneuver with only a sphygmomanometer are that the expiratory effort is not measured and standardized and that a continuous blood pressure signal is not recorded. These drawbacks may limit accuracy because expiratory effort affects blood pressure response (21,23) and because calculation of pulse amplitude ratio, a continuous variable, requires a continuous signal. These considerations may contribute to a lack of widespread clinical use of the technique.…”
Section: Discussionmentioning
confidence: 99%
“…The Finapres system sometimes produced different measurements of BP compared with an ambulatory Omron blood pressure cuff. The manufacturer (Finapres Medical Systems) and findings from other authors (1,4,14) indicated that the Finapres is suitable in situations where changes in BP are more important than absolute values. To obtain accurate absolute values for recordings of BP and CO, the Finapres equipment must be calibrated at each use (14).…”
Section: Discussionmentioning
confidence: 94%
“…The use of echocardiography required the employment of a qualified echocardiographer, a luxury that many university teaching laboratories do not have. Such novel approaches for the teaching of cardiovascular physiology are rare.The Finapres finger cuff is a recording system that provides continuous and concurrent calculations of CO, BP, SV, TPR, and HR (1,13,14). It is traditionally used in research settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation